Grey literature citations in top nursing journals: a bibliometric study - Woods, Stephen (J Med Libr Assoc, 2020)
OBJECTIVE: As access to information grows in tandem with the growth of the Internet, access to grey literature also increases. Because little is known about the use of grey literature in nursing journals, the authors investigated the prevalence and types of grey literature citations in top nursing journals. METHODS: We analyzed all citations (n=52,116) from articles published in 2011 in 6 top nursing journals selected from the Medical Library Association’s Nursing and Allied Health Resource Section’s 2012 “Selected List of Nursing Journals.” Grey literature citations were identified and categorized by type. RESULTS: Grey literature accounted for 10.4% of citations across all 6 journals. Publications from governments (54.3%) and corporate organizations (26.8%) were the most common types of grey literature. CONCLUSION: The substantial citation of grey literature in nursing journals shows that nursing scholars seek and use this category of information. These findings have implications for teaching and learning among nursing researchers and the information professionals who serve the nursing research community.